Project results presentation (deliverable D18) - Macedo, Joaquim (2008)
This document is a report which collects together the CYCLOPS project results for dissemination to different interested audiences such as Grid communities and Civil Protection agencies. It also reports on national and international initiatives and projects, SMEs, training activities and related projects. The structure of this document shows the approach used in the project. Following an introduction, it describes a set of related projects, namely grid- based technologies/EGEE, risk management, and GMEs-based services. It then presents the business of Civil Protection and the use cases selected. These highlight the grid requirements for Grid-based CP applications. The research strategies and enhancements needed for the EGEE infra-structure are identified, based on the use cases. Dissemination of training and knowledge to different communities are also key points of the project.